Growth of internodes and branching of a tomato plant - V. G. Korol (Овощи России, 2022)
Relevance. A significant influence on the use of the volume of greenhouses by a tomato plant is its height, which consists of the length of the internodes of monopodial and sympodial shoots. The use of the volume of greenhouses in the cultivation of tomato crops is a relevant and important topic. Currently, tomatoes are grown in greenhouses of various heights and designs. Greenhouses of different sizes, heights and types of cover are used in a farmer's market. And here the height of tomato plants is of decisive importance. Mostly indeterminate plants are grown, limiting their growth to a certain number of inflorescences, less often determinant plants. When grown in modern industrial greenhouses and the vegetation period is 1012 months a year, preference is given to tall indeterminate tomato hybrids that have almost continuous growth due to the formation of more and more sympodial shoots and high yield potential.Methods. The studies were carried out in a winter glazed greenhouse. The tomato culture was grown in an extended rotation (from January to November) on a coconut substrate with drip irrigation. Tomato hybrids of domestic and foreign selection with determinant and indeterminate types of growth were grown. Phytocenosis density is 2.8 plants/m2, from April to September it thickened up to 3.4 plants/m2 due to the formation of additional shoots. All observations were carried out according to generally accepted methods. Results. The variety grown in protected ground depends on the growing conditions. A pattern was established for the length of the internodes of sympodial shoots in indeterminate tomato hybrids, the third internode is longer than the first two. The correlation coefficient between the length of the sympodial shoot and the length of the third internode is 0.85 points. The enhanced growth of the last internode is caused by the growth of the shoot of the next order. In this case, the removal of the leaf above the inflorescence is 2-5 cm. The correlation coefficient between the length of the third internode and the removal of the leaf above the inflorescence is 0.71 points. A pattern was established for the length of the leaves and the development of stepchildren in the sympodial shoot.